Clinical profile, manifestation, and treatment of dermatophytosis patients at Ngoerah Hospital Bali in 2021-2023 - Kevin Jonathan Djuanda; I.G.A.A. Dwi Karmila; Kevin Jonathan Djuanda (Indonesian Journal of Biomedicine and Clinical Sciences, 2026)
Dermatophytosis is a common superficial fungal infection of keratinized tissues, caused by the fungal family of Microsporum, Epidermophyton, and Trichophyton. It is highly prevalent in tropical regions due to favorable environmental conditions. Local hospital-based data are still needed to describe the clinical pattern of dermatophytosis in Bali. This study aimed to describe the clinical profile, manifestations, laboratory findings, and treatment of dermatophytosis patients treated at the Dermatology and Venereology Outpatient Clinic of Ngoerah Hospital Bali. This descriptive observational study utilized a cross-sectional retrospective design, analyzing medical records of dermatophytosis patients treated since January 2021 to December 2023, and the data were analyzed descriptively. A total of 135 patients were included, with a mean patient age of 30.4 ± 17.5 years old (range 1–73 years old), most cases occurring in females (53.3%), students (35.6%), and showed high prevalence in the 25-44 age group. The majority of patients live in private residences (57%) with the primary transmission route being intrafamilial contact (39.3%). Based on 153 clinical presentations, the most frequent type was tinea corporis (39.2%), followed by tinea cruris (19.0%), tinea unguium (19.0%), and tinea capitis (18.3%). The potassium hydroxide (KOH) examination was documented in 124 patients and fungal culture results were available in 99 patients. Dermatophytosis remains a significant health concern, with tinea corporis as the predominant type in our study. Antifungal systemic and topical treatment were used in this study. Awareness and early diagnosis are essential for effective disease control.